Evaluating English Training Program for The Local People of Kampung Inggris Kebumen Based On Cipp - Hastri Firharmawan; Alek Andika (LPPM IAINU Kebumen, 2019)
Evaluating a program is an important process by which program administrators can see the program effectiveness and make right decision about the program. This study was to evaluate the effectiveness of the English training program for the local people of KampungInggrisKebumen (KIK) at Jatijajar village, Ayah, Kebumen. The evaluation was conducted qualitatively by using CIPP evaluation model which focused on evaluating contexts, inputs, processes, and products of the program. The research involved the students, the tutors, and the chief of the program. Data were obtained through observation, in depth interview, and analysis of the documents gained. The data were analyzed through four steps, namely: 1) Data collecting, 2) Data reducing, 3) Data serving; and, 4) Concluding or verifying. Data sources triangulation was used for data validating. The research discovered that the program was ineffective due to four main factors. First, the context of teaching-learning was less supportive to the program success. Second, the inputs were in lack of quality. Third, the teachinglearning process did not show good teaching practices. Fourth, the course products did not reflect the program goals.This proves Dunkin’s and Biddle’s theory (1974) that context, presage, process, and product variables are interrelated to affect the success of teaching-learning for a course program.